2022
DOI: 10.5194/gc-5-363-2022
|View full text |Cite
|
Sign up to set email alerts
|

Exploring TikTok as a promising platform for geoscience communication

Abstract: Abstract. With TikTok emerging as one of the most popular social media platforms, there is significant potential for science communicators to capitalize on this success and to share their science with a broad, engaged audience. While videos of chemistry and physics experiments are prominent among educational science content on TikTok, videos related to the geosciences are comparatively lacking, as is an analysis of what types of geoscience videos perform well on TikTok. To increase the visibility of the geosci… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 28 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…Scientists develop different strategies for shaping their discourse practices in digital communication environments (Koivumäki et al, 2020), and emotional appeals and "edutainment"oriented approaches in science communication are seen as having the potential to enable communicators to reach new audiences (Taddicken & Reif, 2020). Zawacki et al (2022) argue that TikTok may function as a platform where educational science videos are able to reach a large audience without much effort. Habibi and Salim (2021) found that short lecture-style videos on TikTok had a significantly higher "watch time" compared to longer lecture-style or experimental videos.…”
Section: Visibility Of Topicsmentioning
confidence: 99%
“…Scientists develop different strategies for shaping their discourse practices in digital communication environments (Koivumäki et al, 2020), and emotional appeals and "edutainment"oriented approaches in science communication are seen as having the potential to enable communicators to reach new audiences (Taddicken & Reif, 2020). Zawacki et al (2022) argue that TikTok may function as a platform where educational science videos are able to reach a large audience without much effort. Habibi and Salim (2021) found that short lecture-style videos on TikTok had a significantly higher "watch time" compared to longer lecture-style or experimental videos.…”
Section: Visibility Of Topicsmentioning
confidence: 99%